Serological evidence of hantavirus infection in rural and urban regions in the state of Amazonas, Brazil - João Bosco Lima Gimaque; Michele de Souza Bastos; Wornei Silva Miranda Braga; Cintia Mara Costa de Oliveira; Márcia da Costa Castilho; Regina Maria Pinto de Figueiredo; Elizabeth dos Santos Galusso; Evaulino Ferreira Itapirema; Luiz Tadeu Moraes de Figueiredo; Maria Paula Gomes Mourão (Memorias do Instituto Oswaldo Cruz, 2012)
Hantavirus disease is caused by the hantavirus, which is an RNA virus belonging to the family Bunyaviridae. Hantavirus disease is an anthropozoonotic infection transmitted through the inhalation of aerosols from the excreta of hantavirus-infected rodents. In the county of Itacoatiara in the state of Amazonas (AM), Brazil, the first human cases of hantavirus pulmonary and cardiovascular syndrome were described in July 2004. These first cases were followed by two fatal cases, one in the municipality of Maués in 2005 and another in Itacoatiara in 2007. In this study, we investigated the antibody levels to hantavirus in a population of 1,731 individuals from four different counties of AM. Sera were tested by IgG/IgM- enzyme-linked immune-sorbent assay using a recombinant nucleocapsid protein of the Araraquara hantavirus as an antigen. Ten sera were IgG positive to hantavirus (0.6%). Among the positive sera, 0.8% (1/122), 0.4% (1/256), 0.2% (1/556) and 0.9% (7/797) were from Atalaia do Norte, Careiro Castanho, Itacoatiara and Lábrea, respectively. None of the sera in this survey were IgM-positive. Because these counties are distributed in different areas of AM, we can assume that infected individuals are found throughout the entire state, which suggests that hantavirus disease could be a local emerging health problem.